2021
DOI: 10.1002/smll.202007576
|View full text |Cite
|
Sign up to set email alerts
|

Pathways towards Boosting Solar‐Driven Hydrogen Evolution of Conjugated Polymers

Abstract: Photocatalytic H2 evolution under solar illumination has been considered to be a promising technology for green energy resources. Developing highly efficient photocatalysts for photocatalytic water splitting is long‐term desired but still challenging. Conjugated polymers (CPs) have attracted ongoing attention and have been considered to be promising alternatives for solar‐driven H2 production due to the excellent merits of the large π‐conjugated system, versatile structures, tunable photoelectric properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 236 publications
(301 reference statements)
0
41
0
1
Order By: Relevance
“…[ 6–8 ] To date, various organic polymers with conjugated skeletons have been developed as photocatalysts for hydrogen evolution. [ 9–11 ] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6–8 ] To date, various organic polymers with conjugated skeletons have been developed as photocatalysts for hydrogen evolution. [ 9–11 ] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] To date, various organic polymers with conjugated skeletons have been developed as photocatalysts for hydrogen evolution. [9][10][11] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [12][13][14] Many studies revealed that designing a donor-acceptor (D-A) molecular structure is an efficient strategy to boost the photocatalytic activity of conjugated polymer photocatalysts, [15][16][17][18] since the intrinsic electron push-pull effect in a D-A conjugated polymer could promote the separation of light-induced hole/ electron.…”
mentioning
confidence: 99%
“…Several papers have reviewed the applications of 2D nanomaterials, [2,3,6,14,15] conjugated networks, [4,7,12,16,17] porous organic polymers (POPs), [5,13,[18][19][20][21][22] hypercrosslinked porous polymer (HCPs), [23] porous aromatic frameworks (PAFs), [24] and carbonaceous materials, [25,26] in which CTFs are involved as a subclass material, and specific fields deploying CTFs-related systems, [9,11,27] such as separation [28][29][30][31] and catalysis, [10,[32][33][34] while systematic summarization and comparison of graphitic aza-fused π-conjugated networks including and beyond CTFs have rarely been covered. Considering the blossom of the material category related to graphitic aza-fused π-conjugated networks, it is highly required to figure out the pivotal factors in structure-property-application relationship from diverse levels, which will provide guidance in monomer design and synthesis pathway selection to achieve far-reaching applications.…”
Section: Doi: 101002/adma202107947mentioning
confidence: 99%
“…Generally, the photocatalytic activity of these materials is determined by their band structures, charge separation and transfer efficiency, porosity, dispersibility, and so on. [14] Relying on the vast structure-to-property regulating methodologies being developed, the photocatalytic applications of related systems have been witnessed in water splitting, [16,20,34] H 2 O 2 generation, CO 2 reduction, organic coupling reaction, and pollutant degradation.…”
Section: As Catalyst Components In Photocatalysismentioning
confidence: 99%
“…By comparing the properties of the solvent, it seemed that the activity was positively correlated with the polarity. 24 Therefore, methanol was added to compare the effects of solvents with similar structure on the properties. It can be seen from the test results (Fig.…”
mentioning
confidence: 99%